Forecasting of rice blast in Kangra district of Himachal Pradesh - and G.K. SOOD, A.S. KAPOOR, R. PRASAD (Indian Phytopathology, 2004)
The overall rice blast severity during 1997, 1998 and 1999 in Kangra district, Himachal Pradesh was mild to moderate. Rainfall amount and distribution varied greatly within the rice growing season. In all the three years, temperature (18-28 Â°C) and RH (more than 9 h > 90%) during crop season were within the optimum range required for disease development. Analyses of 13 years (1984-1996) weather data revealed that the number of days with RH of >90 % (47 and 27 days) during July to September, number of rainy days in a week and cloudiness were most critical factors in the development of rice blast epidemics during blast years of 1984 and 1992. Moderate to high (10-30%) leaf blast severity in trap nurseries on any susceptible cultivar sown at 15 days interval starting from 1st June or 5-10 per cent leaf blast incidence on trap plants, continued high humidity > 80%, prevalence of low temperature (16-19o C) and maximum temperature (< 28o C) for 6-8 days or cloudy weather and 5-6 rainy days in a week were identified as rice leaf blast rules for predicting blast disease development. Though the quantitative predictive equations developed were not very encouraging some variables viz., temperature, hours RH > 90 %, wetness duration, rainy days and rainfall amount in different combinations were found to be useful in the prediction of rice blast. Validation of rice blast rules during 1999 revealed 50 per cent reduction in rice blast in managed plots after forecasting and grain yields improved by 30 to 40 per cent.